Exploring quantitative indices to characterize piano timbre with precision validated using measurement system analysis - Zhuang, Yuan; Yang, Shuo (Frontiers in Psychology, 2024)
Timbre in piano performance plays a critical role in enhancing musical expression. However, timbre control in current piano performance education relies mostly on descriptive characterization, which involves large variation of interpretation. The current study aims to mitigate the limitations by identifying quantitative indices with adequate precision to characterize piano timbre. Methods: A total of 24 sounds of G6 were recorded from 3 grand pianos, by 2 performers, and with 4 repetitions. The sounds were processed and analyzed with audio software for the frequencies and volumes of harmonic series in the spectrum curves. Ten quantitative timbre indices were calculated. Precision validation with statistical Gage R&R analysis was conducted to gage the repeatability (between repetitions) and reproducibility (between performers) of the indices. The resultant percentage study variation (%SV) of an index must be ≤10% to be considered acceptable in characterizing piano timbre with enough precision. Results: Out of the ten indices, four indices had acceptable precision in characterizing piano timbre with %SV ≤10%, including Square Sum of Relative Volume (4.40%), Frequency Weighted Arithmetic Mean of Relative Volume (4.29%), Sum of Relative Volume (3.11%), and Frequency Weighted Sum of Relative Volume (2.09%). The novel indices identified in the current research will provide valuable tools to advance the measurement and communication of timbre and advance music performance education.